Studying product diffusion based on market coverage. Issue 4 (December 2016) - Anand, Adarsh; Agarwal, Mohini; Bansal, Gunjan; Garmabaki, A.
Abstract Market coverage is an important attribute for determining the success of a product. The larger the market covered by a product is, the higher the amount of sales for that product will be. Market coverage strategies thus contribute to the success of a product in tapping the market. In this study, we emphasize the impact of market coverage on the rate of adoption in determining product sales. New product diffusion models based on the market covered are proposed. A methodological approach of weighted criteria is implemented to evaluate and rank the proposed models. The analysis is conducted on real-life sales datasets.